RFID‐based stent‐graft dynamic assessment for health cares. Issue 1 (1st January 2017) - Wei, Lifang; Yang, Changcai; Chen, Riqing
Abstract : With the rapid development of RFID technologies, it is possible to make the three‐dimensional dynamics of stent graft. The authors design an RFID‐based method for automatic assessment of stent‐graft dynamic. The posterior probability from correspondence between two tag sets in successive frames is calculated to estimate what degree the observed RFID tag coincides with others. The results from simulation experiments show the superior performance of the proposed method.